Active Trailer Braking System Design with Linear Matrix Inequalities Based Multi-Objective Robust LQR Controller for Vehicle-Trailer Systems - Sever, M.; Kaya, E. E.; Arslan, M. S.; Yazici, H. (IEEE, 2016)
An Active Trailer Braking system is designed for the mitigation of trailer sway. Motion of the vehicle-trailer system on the horizontal plane with three degrees of freedom is modeled. Variations on the dynamic behaviors are studied due to the changes in longitudinal velocity. Then, performance objectives of controller is specified in terms of robust stability and lower bound of damping ratio for a prescribed longitudinal velocity range. Linear Matrix Inequalities based robust multio-bjective LQR controller is designed with constraints on closed-loop pole locations and guarantee of robust stability. Finally, superiority of the designed controller is shown by using some numerical comparison with a classical Algebraic Riccati Equation based LQR design reported in the literature.
Keywords: CAR-CARAVAN COMBINATION; Computer Science; Robotics